Controlling Electrical Conductance through a π‐Conjugated Cruciform Molecule by Selective Anchoring to Gold Electrodes. Issue 48 (7th October 2015) - Huang, Cancan; Chen, Songjie; Baruël Ørnsø, Kristian; Reber, David; Baghernejad, Masoud; Fu, Yongchun; Wandlowski, Thomas; Decurtins, Silvio; Hong, Wenjing; Thygesen, Kristian Sommer; Liu, Shi‐Xia
Abstract: Tuning charge transport at the single‐molecule level plays a crucial role in the construction of molecular electronic devices. Introduced herein is a promising and operationally simple approach to tune two distinct charge‐transport pathways through a cruciform molecule. Upon in situ cleavage of triisopropylsilyl groups, complete conversion from one junction type to another is achieved with a conductance increase by more than one order of magnitude, and it is consistent with predictions from ab initio transport calculations. Although molecules are well known to conduct through different orbitals (either HOMO or LUMO), the present study represents the first experimental realization of switching between HOMO‐ and LUMO‐dominated transport within the same molecule. Abstract : Singled out : For the first time, it has been demonstrated that two distinct charge‐transport pathways, through a cruciform molecule at the single‐molecule level, can be tuned by chemically controlling the anchoring sites. Upon in situ cleavage of the triisopropylsilyl group, complete conversion from the NAu junctions into CAu junctions is achieved with a conductance increase of more than one order of magnitude. TBAF=tetra‐ n ‐butylammonium fluoride.